1988
DOI: 10.1210/jcem-67-4-727
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Thyroxine-Binding Globulin (TBG) Gene in Six Unrelated Families With Complete TBG Deficiency*

Abstract: T4-binding globulin (TBG) is a glycoprotein of hepatic origin which transports thyroid hormone in serum. Inherited TBG defects in man are X-chromosome linked and are expressed in hemizygotes as complete deficiency, partial deficiency, or excess. Since TBG is not necessary for thyroid hormone action, affected subjects are healthy. Using DNA probes for human TBG, we searched for restriction fragment length polymorphisms in six affected males belonging to 6 unrelated families with inherited complete TBG deficienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…DNA was digested to completion with Eco RI (New England Biolabs, Beverly, MA), then subjected to 1.0% agarose gel electrophoresis, and following denaturation was transferred onto nitrocellulose paper (Southern blot). Hybridization was carried out under conditions previously described (43), using the hTR(B, cDNA probe pheA4 (14) which is complementary to all exons (two 5'-noncoding and eight coding) (27). The probe covers 80 nucleotides (30%) of the last coding exon (exon 8).…”
Section: Methodsmentioning
confidence: 99%
“…DNA was digested to completion with Eco RI (New England Biolabs, Beverly, MA), then subjected to 1.0% agarose gel electrophoresis, and following denaturation was transferred onto nitrocellulose paper (Southern blot). Hybridization was carried out under conditions previously described (43), using the hTR(B, cDNA probe pheA4 (14) which is complementary to all exons (two 5'-noncoding and eight coding) (27). The probe covers 80 nucleotides (30%) of the last coding exon (exon 8).…”
Section: Methodsmentioning
confidence: 99%
“…In a study of six unrelated males with TBG-CD, we noted no differences in the number or pattern of TBG gene fragments generated with 11 restriction endonucleases and analyzed using both a TBG cDNA and a TBG genomic DNA (gDNA) probe (11). These data indicated that TBG-CD is not usually due to deletions or rearrangements of the TBG gene.…”
mentioning
confidence: 88%
“…Nineteen were French Canadians, 8 were Caucasians of European but not French origin, 3 were Mexican, 3 were Australian Aborigines, and 2 were Japanese. Three of the French Canadian subjects with TBG-C were each unaffected relatives of families with TBG-CD (CD1, CD2, and CD3) (11). Data on the inheritance pattern of TBG-CD in the 7 families of French Canadian origin has been previously reported (12).…”
Section: Subjectsmentioning
confidence: 98%
See 1 more Smart Citation
“…Serum total T4 (TT4), total T3 (TT3), free T4 (FT4) and TSH were measured with commercial kits. DNA amplificationand sequencing of TBG gene Genomic DNA was obtained by extraction from white blood cells, as previously described [15]. DNA from the propositus served as a template to amplify the coding regions (Exon 0 through Exon 4) and the adjacent exon/intron junctions of the TBG gene by the polymerase chain reaction (PCR) with Taq DNA polymerase (Perkin-Elmer Cetiis Corp., Norwalk, CT), using Parkin-Elmer Cetus Thermal Cycler (model PJ 1000), under the conditions and with the oligonucleotide primers described previously [1 1 ].…”
Section: Methodsmentioning
confidence: 99%